Vegetative, metabolic and immune accompaniments of changes in the electrokinetic index of the buccal epithelium under the influence of therapeutic factors - Kyrylenko, Iryna; Fediaieva, Svitlana; Miesoiedova, Vita; Popadynets’, Oleksandr; Żukow, Xawery (Journal of Education, Health and Sport, 2022)
Background. In previous studies, we have shown that electrokinetic index of buccal epithelium (EKI) correlated with some functional and metabolic parameters. Subsequent studies have shown that сhanges in EKI correlated with changes in some parameters of EEG, HRV, hemodynamics, metabolism, immunity and fecal microbiocenosis. Further research in this direction was continued on a significantly increased contingent of patients and with the involvement of new methods and factors of influence. This message starts the presentation of the obtained results. Material and methods. Under a observations were 44 men (49±15 years) and 30 women (51±13 years) without clinical diagnosis or with chronic pyelonephritis in the phase of remission (23 men). We registered caused by the various therapeutic factors changes in EKI, state of the vegetative and hormonal regulation as well as immunity and metabolism, then calculated relationships between changes. Results. In 49 patients the changes in EKI were in the range of ±2,5%, in 19 people EKI increased by more than 2,5% (M±SD=+4,0±1,6%), while in 9 people decreased by more than 2,5% (-4,2±1,7%). The canonical correlation between changes in EKI, on the one hand, and HRV and immunity parameters, on the other, is moderate: R=0,478; p=0,023. The method of discriminant analysis revealed 10 immune and 6 HRV parameters as well as triglycerides and cholesterol, whose changes are characteristic of multidirectional changes in EKI. Conclusion. Electrokinetic index of buccal epithelium responds to therapeutic factors in different directions, accompanied by characteristic changes in a number of parameters of HRV, immunity and metabolism.